Consistent Partial Matching of Shape Collections via Sparse Modeling - Cosmo, Luca; Rodola, Emanuele; Albarelli, A.; Memoli, F.; Cremers, D. (Computer Graphics Forum, 2017)
Recent efforts in the area of joint object matching approach the problem by taking as input a set of pairwise maps, which are then jointly optimized across the whole collection so that certain accuracy and consistency criteria are satisfied. One natural requirement is cycle-consistency—namely the fact that map composition should give the same result regardless of the path taken in the shape collection. In this paper, we introduce a novel approach to obtain consistent matches without requiring initial pairwise solutions to be given as input. We do so by optimizing a joint measure of metric distortion directly over the space of cycle-consistent maps; in order to allow for partially similar and extra-class shapes, we formulate the problem as a series of quadratic programs with sparsity-inducing constraints, making our technique a natural candidate for analysing collections with a large presence of outliers. The particular form of the problem allows us to leverage results and tools from the field of evolutionary game theory. This enables a highly efficient optimization procedure which assures accurate and provably consistent solutions in a matter of minutes in collections with hundreds of shapes.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Computer Graphics I.3.5 Computational Geometry and Object Modelling Shape Analysis; intrinsic geometry; shape collections; shape matching